The Mannose Receptor in Regulation of Helminth-Mediated Host Immunity - van Die, Irma; Cummings, Richard D. (Frontiers in Immunology, 2017)
Infection with parasitic helminths affects humanity and animal welfare. Parasitic helminths have the capacity to modulate host immune responses to promote their survival in infected hosts, often for a long time leading to chronic infections. In contrast to many infectious microbes however, the helminths are able to induce immune responses that show positive bystander effects such as the protection to several immune disorders, including multiple sclerosis, inflammatory bowel disease, and allergies. They generally promote the generation of a tolerogenic immune microenvironment including the induction of type 2 (Th2) responses and a sub-population of alternatively activated macrophages (AAMs). It is proposed that this anti-inflammatory response enables helminths to survive in their hosts, and protects the host from excessive pathology arising from infection with these large pathogens. In any case there is an urgent need to enhance understanding of how helminths beneficially modulate inflammatory reactions, to identify the molecules involved and to promote approaches to exploit this knowledge for future therapeutic interventions. Evidence is increasing that C-type lectins play an important role in driving helminth-mediated immune responses. C-type lectins belong to a large family of calcium-dependent receptors with broad glycan-specificity. They are abundantly present on immune cells such as dendritic cells and macrophages, which are essential in shaping host immune responses. Here we will focus on the role of the C-type lectin Macrophage Mannose Receptor (MR) in helminth-host interactions, which is a critically understudied area in the field of helminth immunobiology. We give an overview of the structural aspects of the MR including its glycan-specificity, and the functional implications of the MR in helminth-host interactions focusing on a few selected helminth species.